ALTERATIONS IN PLASMA FIBRINOGEN DURING LIFE EVENTS IN WOMEN - Khan, Mir Hassan; Khan, Jahangir A; Begum, Nazakat; Maqbool, S Fali; Rana, Nighat (Journal of Ayub Medical College Abbottabad, 1996)
Changes in plasma fibrinogen levels were observed in women during pregnancy, labour, postmenopause and after taking oral contraceptives. Mean fibrinogen level was highest at delivery, higher during pregnancy and high in postmenopausal women. Women who ceased menstruation with contraceptive drugs had lower values of plasma fibrinogen than control group.